The Fate of Lithuanian Jews’ Assets during the Second World War - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2004)
The cultural assets of Lithuanian Jews were registered by the staff of Rosenberg headquarters whose branches were established in Vilnius and Kaunas. The most valuable manuscripts, incunabula, museum pieces, collections of Jews folklore, photographs, newspaper collections and other assets were moved to Germany. The less valuable Judaica was destroyed on the spot; it was burnt and taken to paper mills. There were also the archives of Jewish communities, their libraries registered and expropriated, the synagogues registered all over Lithuania. They fell under the control of local administrations, i.e. local district administrators, the elders, burgomasters and other officials, some of them became temporary storehouses of the remaining Jewish assets, or were transferred to schools and other institutions.